340TiPA multicenter, randomized, controlled, phase II trial exploring adjuvant combined therapy of apatinib and SHR-1210 (anti-PD-1), in patients with hepatocellular carcinoma at high risk of recurrence after radical resection. (24th November 2019) - Yan, S; Zhang, Y; Bi, X; Zhao, J; Du, S; Huang, Z; Zhang, Y; Liu, D; Li, Z; Zhou, J; Cai, J; Zhao, H
Abstract: Background: Hepatocellular carcinoma (HCC) is the most common malignancy with high rates of recurrence and metastasis after radical resection. Vascular invasion, including portal vein tumor thrombus (PVTT) and microvascular invasion (MVI), and microsatellite lesions are two significant risk factors of postoperative recurrence and metastasis for HCC. Therefore, it is necessary to discover adjuvant therapies for patients with these risk factors. Anti-angiogenesis therapy combined with immunotherapy has demonstrated clinical benefits in multiple advanced solid neoplasms, including HCC. An exploratory phase Ib study (NCT02942329) proved that combined therapy of apatinib (250mg QD) and anti-PD-1 drug, SHR-1210 (200mg Q2W) was well tolerated and had preliminary efficacy in advanced HCC. Trial design: This multicenter, randomized, controlled, phase II study will evaluate the safety and efficacy of adjuvant combined therapy of apatinib and anti-PD-1 drug, SHR-1210, compared with hepatic arterial infusion (HAI) chemotherapy, in patients with HCC at high risk of recurrence after radical resection. 200 patients, aged >18 years, Child-Pugh score 0 or 1, with histologically confirmed primary HCC, BCLC stage A or B diseases that are radical resected without other prior therapy for HCC and who are found to have microsatellite lesions, microvascular invasion or PVTT involved in second-order branch or above by preoperative imaging examination or postoperative pathological findings will be recruited and randomized (1:1) to receive apatinib (250mg QD) and SHR-1210 (200mg Q2W) for 6 months, or 2 times of standard HAI treatments (epirubicin 80-100mg or epirubicin 50mg+oxaliplatin 50mg). The primary endpoint is to compare recurrence-free survival and secondary endpoints include overall survival, safety, 1, 2, 3-year recurrence rate and Quality of Life score (QoL). Survival follow-up will continue for up to 3 years. The study is ongoing. Clinical trial identification: NCT 03839550. Legal entity responsible for the study: National Cancer Center/Cancer Hospital. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.